Falibras Translator: Towards More Health Care Humanization for Deaf People - Marcolino, Vitor; Franco, Natália; Brito, Patrick; Coradine, Luis (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2015)
This work presents Falibras, a translation system between Portuguese and Brazilian Sign Language (LIBRAS) that aims to help both, deaf people and hearers, in trying to communicate. Falibras offers an important tool to provide easy communication and more humanization of health care for deaf people. This paper presents some of the re-engineered artifacts of the Falibras system. Moreover, a discussion about its applicability in e-Health is also presented. Among its main applications, this system supports language learning, both sign and writing language, autonomy for deaf people and humanization in health care. Falibras also gives the possibility of generalizing the translation process in order to allow the translation from any written language to any target language (written, spoken or signaled). Thus, the translation mechanism does not limit the languages involved.